A universal basic income in the superstar (digital) economy - White, Andrew (Taylor & Francis, 2018)
This paper argues that the structural logic of the digital economy is to widen inequality, not only through its increasing automation of jobs but also in its efficiency in delivering ever greater profits to a smaller number of already-enriched organisations and individuals. Remedial actions that might be taken to mitigate the effects of some of the digital economy’s structural flaws are interrogated here, with a particular focus on universal basic income (UBI) and stake-holding schemes. The paper considers whether the digital economy’s inherent problems are of such magnitude that some sort of financial support for workers to buttress long periods of idleness, or to enable them to take risks in increasingly volatile and unstable global markets, is both desirable and politically feasible.